Developing critical reading module using integrated learning content and language approach - Annas Surdyanto; Wiwit Kurniawan (Universitas Syiah Kuala, 2020)
The purpose of this research is to compile a teaching material in the form of critical reading modules that are effective, valid, and practical for English major students. Teaching materials developed are based on CLIL (Content and Language Integrated Learning) learning and are oriented towards students’ critical thinking skills. CLIL not only emphasizes language skills but also on how learning content can provide a stimulus to think and understand the goals of learning. This study uses a Research and Development (RD) approach. The development model used is the ADDIE (Analyse, Design, Development, Implement, Evaluation). The results of the study show that the module that has been developed is valid, practical and effective. The validity of the module reaches a very good category based on the expert’s and validator’s evaluation. The practicability of the module is categorized as very good according to the students’ responses, observation on the implementation, and lecturer’s evaluation. The module effectivity reaches a very good category based on the students’ achievement on the tests.